Emission colours of bistable photochromic compounds: Ce-doped alkaline (Rb, K, Na)–indium fluorides. Issue 18 (1st August 2022) - Gaudon, Manuel; Andron, Ines; Demourgues, Alain; Rodriguez, Vincent; Fargues, Alexandre; Durand, Etienne; Chiron, Anthony; Frayret, Christine; Jubera, Véronique
Abstract : The structural and spectroscopic properties of Ce 3+ -doped K3 InF6, K2 NaInF6 and Rb2 KInF6 compounds are investigated. Abstract : The structural and spectroscopic properties of three Ce 3+ -doped A3 InF6 compounds (with A + = Rb +, K +, Na + ) are investigated. Containing indium, they all exhibit 2Ce 3+ + In 3+ ⇔ In + + 2Ce 4+ redox processes induced by UV irradiation between Ce 3+ and In 3+ cations. The photochromo-luminescent behaviour and associated kinetics, with the Ce 3+ and In + ion emission quenching through the redox equation, respectively, are investigated. Our studies highlight that different mechanisms (surface vs. bulk) need be considered to explain the decrease in the blue (Ce 3+ ) and orange (In + ) emission curves. Moreover, the comparison of Ce 3+ -doped Rb2 KInF6, K2 NaInF6 elpasolites and K3 InF6 cryolite spectral distributions shows that changing the nature of the alkali cation makes colour tuning possible. The shift of the Ce 3+ and In + colour emissions between the three as-prepared compounds is mainly due to the variation in the ionic-covalent nature of the chemical bonds around the active cation sites. The final calculated optical difference between the two bistable states varies from 0.31 to 0.48 depending on the alkali subnetwork.